2017
DOI: 10.1016/j.watres.2017.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiltration as tertiary treatment method for removing trace pharmaceutically active compounds in wastewater from wastewater treatment plants

Abstract: The ever-increasing occurrence and persistence of pharmaceutically active compounds (PhACs) in soils, sediments, drinking water supplies and wastewater effluents are a matter of serious environmental concern for governments and researchers worldwide. Nanofiltration as tertiary treatment method can be a viable and practical tool to remove these pollutants from aquatic environments. However, organic matter present in water sources can foul the membrane surface during operation, thus being potentially able to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(50 citation statements)
references
References 73 publications
0
39
0
2
Order By: Relevance
“…To achieve OMPs removal, the most frequently used advanced technologies include activated carbon adsorption (Benstoem et al, 2017;Boehler et al, 2012;Meinel et al, 2015), advanced oxidation processes (Bourgin et al, 2017;Miklos et al, 2018;Yao et al, 2018) and membrane processes (Garcia-Ivars et al, 2017;Sahar et al, 2011;Snyder et al, 2007). Adsorption performances vary according to the type and dose of activated carbon (Kårelid et al, 2017), the operational conditions (Frank et al, 2015;Streicher et al, 2016) and the quality and composition of the water (Zietzschmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve OMPs removal, the most frequently used advanced technologies include activated carbon adsorption (Benstoem et al, 2017;Boehler et al, 2012;Meinel et al, 2015), advanced oxidation processes (Bourgin et al, 2017;Miklos et al, 2018;Yao et al, 2018) and membrane processes (Garcia-Ivars et al, 2017;Sahar et al, 2011;Snyder et al, 2007). Adsorption performances vary according to the type and dose of activated carbon (Kårelid et al, 2017), the operational conditions (Frank et al, 2015;Streicher et al, 2016) and the quality and composition of the water (Zietzschmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The flux Water Environment Research, Volume 90, Number 10 -Copyright © 2018 Water Environment Federationacross NF270 was stable, while its rejection of PFHxA was very sensitive to the variation of initial feed pH. In contrast, NTR7450 showed a very good stability on rejection rate, whereas its flux was very sensitive to changing initial feed pH Garcia-Ivars et al (2017). implemented three NF membranes (TFC-SR2, to study both the removal of trace pharmaceuticals (PhACs) and the fouling mechanisms of each membrane through varying feed pH.…”
mentioning
confidence: 94%
“…Among them, MF and UF are commonly used as pretreatment for NF and RO, a common practice for further concentration of nutrients [ 16 , 17 ]. Previous studies showed that clean permeates could be obtained for recycling by the NF and RO processes [ 8 , 18 , 19 ], and the concentrates with concentrated nutrients and reduced volume could be obtained as a valuable organic fertilizer [ 18 , 20 , 21 , 22 ]. Additionally, studies showed that the combined process of NF and RO (NF + RO) had lower energy consumption and better nutrient concentration performance than the single process, either NF or RO [ 23 ].…”
Section: Introductionmentioning
confidence: 99%